Structural equation modeling of internet of things (IoT) adoption for Indonesian Village-Owned Enterprises (BUMDes) - Bustami Usman; Ilham Sentosa; Febri Nurrahmi (Universitas Negeri Yogyakarta, 2021)
This study seeks to examine the antecedents of Internet of Things (IoT) intention and adoption of Indonesian village-owned enterprises (Badan Usaha Milik Desa, BUMDes) by applying the Technology Acceptance Model (TAM). The respondents comprised 237 managers and staff of BUMDes in Aceh, Indonesia. A questionnaire was designed to examine perceived usefulness of IoT on the product and service empowerment, perceived ease of use of IoT, and perceived credibility on IoT, intention to use the technology, and adoption of IoT to the community empowerment in the village setting. The data were analyzed using partial least squares structural equation modeling (PLS-SEM). The generated model of IoT showed three significant direct paths between perceived usefulness, perceived credibility on the IoT, and intention as well as between intention and adoption. The re-specified model of IoT adoption indicated two significant direct paths (perceived usefulness to intention and intention to adoption) and introduced three new paths (direct paths from perceived usefulness, perceived ease of use, and perceived credibility to adoption). The final model also established partial mediating effects of intention between Perceived Usefulness, Perceived Ease of Use, and IoT adoption. This study suggests the relevance of TAM to explain IoT adoption in Indonesian village-owned companies.